ANALISIS SEMIOTIKA IKLAN WARDAH BEAUTY MOVES YOU MELALUI MEDIA YOUTUBE - Syahruni , Syahruni; Hadawiah, Hadawiah; Zelfia, Zelfia (UNIVERSITAS MUSLIM INDONESIA, 2022)
This study discusses the Semiotic Analysis of Wardah Beauty Moves You advertisements which aired through the Wardah Beauty YouTube channel published since October 2021 with a duration of 60 seconds. With the development of technology, YouTube has become one of the most practical and easily accessible social media, so that it becomes the most popular site and is watched by thousands of people every day. The advertisement emphasizes that women's beauty can be a driving force for change that can have an impact and benefit on the environment. This study aims to determine the representation of symbols and meanings of beauty in Wardah Beauty Moves You advertisement, using a qualitative approach with virtual ethnographic methods. Researchers analyzed advertisements by collecting data from YouTube and then taking pictures of several scenes related to the meaning of beauty in the advertisement. The results of this study indicate that the representation of the symbol of beauty in the advertisement is showing Dewi Sandra as Wardah's brand ambassador who can represent the beauty of Indonesian women. The meaning of women's beauty is that they are capable of driving change according to the ad's tagline, namely #BeautyMovesYou. The beauty of women shown in advertisements is not monotonous in terms of beauty standards for Indonesian women in general, namely having white skin and long straight hair. However, the advertisement wants to show that in fact beauty is not only physical beauty. The meaning of beauty varies depending on the perspective of people.